Make or buy strategy and origin of sourcing materials and their relationship with firm performance - Mohamed, Zainal Abidin; Abdullah, Haim Hilman; Othman, Rozhan; Uli, Jegak (World Business Institute, 2009)
The paper presents a study relating to the strategic decision of ‘make’ or ‘buy’ to organizational performance, and whether it is related to the origin of the resources used on manufacturing firms in Malaysia. Convenience sampling was done and 314 companies responded. The findings indicate that there was no significant difference between the performance of companies that ‘make’ or ‘buy’. But when these two groups were further scrutinised based on the origin of their resources used, sourcing from developed and developing countries do have effects on company performance. The make or buy decisions have become strategic in nature and the sourcing from different destinations have significant relation with performance. Now that globalisation is common, choosing where your resources come from (to ‘buy’ or to ‘make’) can also be a strategic factor. The findings may add another dimension for consideration in the strategy formulation process.